A Handle on Consciousness: The Asymmetry of Consciousness - Goutos, George (Journal of NeuroPhilosophy, 2024)
The mystery of consciousness, especially the question of how we each experience our own unique, first-person perspective, is something that has perplexed scientists for centuries and philosophers for millennia. In the vast complexity of the human brain is a three-pound universe teeming with neurons and synapses. Yet somehow, amidst all this biological machinery, emerges the wondrous phenomenon of consciousness. This raises not one, but two intriguing puzzles. First, there's the symmetric challenge: Why would any physical state become sentient? It's like asking why any light bulb, plugged into any socket, suddenly glows. But the asymmetric challenge is where things get more personal and perplexing: Why does my specific, individual first-person perspective exist at all? Why do I experience my thoughts and my feelings? That’s like asking why does one specific light bulb represent ‘me’? This exploration delves into this enigma, highlighting the inherent uniqueness of each person's first-person perspective. It’s evident that we have no current theories that even come close to an explanation. We need a robust theory, one that will not only explain consciousness but can also fully explain the distinct and deeply personal nature of individual consciousness.